The Palgrave Handbook of Family Policy 2020
DOI: 10.1007/978-3-030-54618-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Earner Family Policies at Work for Single-Parent Families

Abstract: This chapter sets out to examine how family policies differently affect the poverty rate of single-parent families versus couples with children and also probes whether or not there is a premium—or penalty—for single parents. This is based on a literature review and analysis of a number of comparative family policy data infrastructures. Although single parents were found to benefit from child income support, parental leave, and ECEC, important differences were found. The evidence is strong that child income sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Since a monthly Food Insecurity in Employed Lone Mother Households income is guaranteed, the administrative burden of these programmes is low. Additionally, research has shown that these policies can both reduce poverty (National Academies of Sciences, Engineering, and Medicine, 2019) and income volatility among all families (Shaefer et al, 2018), but can be especially effective at reducing poverty among lone parent families (Maldonado and Nieuwenhuis, 2020). Recently, the U.S. has moved toward implementing a child allowance, although temporarily.…”
Section: Discussionmentioning
confidence: 99%
“…Since a monthly Food Insecurity in Employed Lone Mother Households income is guaranteed, the administrative burden of these programmes is low. Additionally, research has shown that these policies can both reduce poverty (National Academies of Sciences, Engineering, and Medicine, 2019) and income volatility among all families (Shaefer et al, 2018), but can be especially effective at reducing poverty among lone parent families (Maldonado and Nieuwenhuis, 2020). Recently, the U.S. has moved toward implementing a child allowance, although temporarily.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these policies have made greater progress in the Spanish case, although they have been directed mainly to the needs of dual-earner families, paying less attention to the problems of reconciliation of single-parent families (Almeda et al, 2016). However, it is also true that reconciliation policies, even if they are not focused on single-parent families, can benefit, for example, divorced mothers by linking them to the labour market before separation (Maldonado & Nieuwenhuis, 2020). These differences between the two countries may mean that in Spain, single-parent mothers with a lower educational level can provide greater protection to their children against material deprivation than in Italy.…”
Section: Interpretative and Hypothetical Modelmentioning
confidence: 99%
“…A large body of cross-national and single-country studies has established that well-designed work-family reconciliation policies—mainly publicly supported child care and paid leave—are effective in securing the economic well-being of families (for a review, see Hegewisch and Gornick 2011; Nieuwenhuis and Van Lancker 2020; Gornick and Meyers 2005). A smaller but growing literature demonstrates that work-family reconciliation policies are especially crucial for strengthening employment and earnings among single parents (for a review, see Maldonado and Nieuwenhuis 2020). That said, many studies, primarily in the last 20 years, have reported an important caveat: while “more” public support for childcare is always advantageous for parents and their children, the same is not true of paid leave, for which “more” is not always better.…”
Section: What Work For Single-parent Families? Highlighting Effective...mentioning
confidence: 99%